2016
DOI: 10.3389/fpls.2016.00838
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Flavonols over Hydroxycinnamic Acids Favors Oxidative Damage Protection under Abiotic Stress

Abstract: Efficient detoxification of reactive oxygen species (ROS) is thought to play a key role in enhancing the tolerance of plants to abiotic stresses. Although multiple pathways, enzymes, and antioxidants are present in plants, their exact roles during different stress responses remain unclear. Here, we report on the characterization of the different antioxidant mechanisms of tomato plants subjected to heat stress, salinity stress, or a combination of both stresses. All the treatments applied induced an increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
158
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(172 citation statements)
references
References 82 publications
(109 reference statements)
13
158
0
1
Order By: Relevance
“…From the standpoint of ROS involvement, a number of studies have shown that ROS levels, the expression of different ROS‐scavenging enzymes and the level of different antioxidants display a unique pattern during stress combination that is different than that found to be induced by each of the different stresses applied separately. These changes were reflected in levels of O 2 .‐ , H 2 O 2 , byproducts of lipid peroxidation, expression of enzymes such as SOD, APX, CAT, AOX, peroxidases, glutathione‐S‐transferase, glutathione reductase and GPX, accumulation of antioxidants such as ascorbate, GSH, flavonols, phenolic compounds, alkaloids, tocopherol and carotenoids, and accumulation of osmoprotectants such as proline, glycine betaine, trehalose and sucrose (Keleş and Öncel, ; Rizhsky et al ., ; Rizhsky et al ., ; Giraud et al ., ; Vile et al ., ; Prasch and Sonnewald, ; Rasmussen et al ., ; Li et al ., ; Rivero et al ., ; Suzuki et al ., ; Vuleta et al ., ; Jin et al ., ; Pandey et al ., ; Carvalho et al ., ; Martinez et al ., ). Because the combination of two different stresses imposes on plants a unique set of physiological restrains, it is likely that the ROS signature generated under conditions of stress combination is unique (Figure ).…”
Section: Ros and Stress Combinationmentioning
confidence: 97%
“…From the standpoint of ROS involvement, a number of studies have shown that ROS levels, the expression of different ROS‐scavenging enzymes and the level of different antioxidants display a unique pattern during stress combination that is different than that found to be induced by each of the different stresses applied separately. These changes were reflected in levels of O 2 .‐ , H 2 O 2 , byproducts of lipid peroxidation, expression of enzymes such as SOD, APX, CAT, AOX, peroxidases, glutathione‐S‐transferase, glutathione reductase and GPX, accumulation of antioxidants such as ascorbate, GSH, flavonols, phenolic compounds, alkaloids, tocopherol and carotenoids, and accumulation of osmoprotectants such as proline, glycine betaine, trehalose and sucrose (Keleş and Öncel, ; Rizhsky et al ., ; Rizhsky et al ., ; Giraud et al ., ; Vile et al ., ; Prasch and Sonnewald, ; Rasmussen et al ., ; Li et al ., ; Rivero et al ., ; Suzuki et al ., ; Vuleta et al ., ; Jin et al ., ; Pandey et al ., ; Carvalho et al ., ; Martinez et al ., ). Because the combination of two different stresses imposes on plants a unique set of physiological restrains, it is likely that the ROS signature generated under conditions of stress combination is unique (Figure ).…”
Section: Ros and Stress Combinationmentioning
confidence: 97%
“…Previous studies have shown that flavonoids are powerful antioxidants involved in abiotic stress responses (Nakabayashi et al, 2014;Martinez et al, 2016). Flavonols inhibit the ABA-dependent ROS burst to regulate stomatal movement (Watkins et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This is probably explained by the fact that 2–3 days of LN treatment, as was the case in the present study, is adequate to stimulate the synthesis of phenolic compounds in lettuce. This increased production of phenolic compounds probably occurs via a mechanism that enables plants to resist the oxidative stress resulting from nitrogen deficiency …”
Section: Discussionmentioning
confidence: 99%
“…This increased production of phenolic compounds probably occurs via a mechanism that enables plants to resist the oxidative stress resulting from nitrogen deficiency. 31,32 Phenolic compounds have also been proved to counteract the harmful effects of excess ROS in the human body, which is closely linked to oxidative stress and eventually causes persistent or reversible cellular damage. 3,33 In the present study, the viability of Caco-2 cells decreased in a dose-dependent manner after treatment with H 2 O 2 for 6 h (Fig.…”
Section: Discussionmentioning
confidence: 99%